Receptive Field Remodeling Induced by Skin Stimulation in Cerebellar Neurons in vivo - Jörntell, Henrik; Ekerot, Carl-Fredrik (Frontiers in Neural Circuits, 2011)
The receptive field of a neuron reflects its function. For example, for parallel fiber (PF) inputs in C3 zone the cerebellar cortex, the excitatory and inhibitory receptive fields of a Purkinje cell (PC) have different locations, and each location has a specific relationship to the location of the climbing fiber (CF) receptive field of the PC. Previous studies have shown that this pattern of input connectivity to the PC and its afferent inhibitory interneurons can be fundamentally disrupted by applying direct electrical stimulation to the PFs, paired or unpaired with CF activation, with protocols that induce plasticity in these synapses. However, afferent fiber stimulation, which is typically used in experimental studies of plasticity, set up highly artificial input patterns at the level of the recipient cells, raising the issue that these forms of plasticity potentially may not occur under more natural input patterns. Here we used skin stimulation to set up spatiotemporally more realistic afferent input patterns in the PFs to investigate whether these input patterns are also capable of inducing synaptic plasticity using similar protocols that have previously been described for direct PF stimulation. We find that receptive field components can be added to and removed from PCs and interneurons following brief periods of skin stimulation. Following these protocols, the receptive fields of mossy fibers were unchanged. These findings confirm that previously described plasticity protocols may have a functional role also for more normal patterns of afferent input.